Pengembangan bahan ajar mata kuliah teori musik berbasis google site - Eben H. Telaumbanua; Novita A. Manalu; Roy Hutagalung; Dian N. Siregar (KURIOS, 2023)
The development of teaching materials for music theory courses based on this Google site uses research and development methods. This research procedure adapts the ADDIE development model, namely a development model consisting of five stages consisting of Analysis, Design, Development, Implementation, and Evaluating. The results of the research show that the Google site-based music theory I and II teaching material products are: development of Google site-based music theory I and II teaching materials using the Borg and Gall development method which consists of 7 processes, namely needs analysis, research planning, initial product development, initial field trials, revision of trial results, main product field trials, and final product revisions. The development of music theory I and II teaching materials based on the Google site is able to make students understand the material better by providing additional supporting videos and can also increase students' interest in reading because it can be accessed anytime and anywhere.